Brill's encyclopedia of Buddhism online - Silk, Jonathan A.; Bowring, Richard; Eltschinger, Vincent (Brill, 2020)
"Brill's Encyclopedia of Buddhism is the first comprehensive academic reference work devoted to the plurality of Buddhist traditions across Asia, offering readers a balanced and detailed treatment of this complex phenomenon in six thematically arranged volumes: literature and languages (I, publ. 2015), lives (II, publ. 2019), thought (III, forthcoming 2022), history (IV, forthcoming 2023), life and practice (V, forthcoming 2025), index and remaining issues (VI, forthcoming 2026)" (Cited description, Brill 2021)